Trdmt1 3'-untranslated region functions as a competing endogenous RNA in leukemia HL-60 cell differentiation - Xu,Sha (2021)
Severe blockage in myeloid differentiation is the hallmark of acute myeloid leukemia (AML). Trdmt1 plays an important role in hematopoiesis. However, little is known about the function of Trdmt1 in AML cell differentiation. In the present study, Trdmt1 was up-regulated and miR-181a was down-regulated significantly during human leukemia HL-60 cell differentiation after TAT-CT3 fusion protein treatment. Accordingly, miR-181a overexpression in HL-60 cells inhibited granulocytic maturation. In addition, our “rescue” assay demonstrated that Trdmt1 3′-untranslated region promoted myeloid differentiation of HL-60 cells by sequestering miR-181a and up-regulating C/EBPα (a critical factor for normal myelopoiesis) via its competing endogenous RNA (ceRNA) activity on miR-181a. These findings revealed an unrecognized role of Trdmt1 as a potential ceRNA for therapeutic targets in AML.